Penile cancer epidemiology and risk factors: a contemporary review. Issue 2 (March 2019) - Douglawi, Antoin; Masterson, Timothy A.
Abstract : Purpose of review: Our objective is to present an overview of epidemiologic, clinical, and molecular risk factors with a focus on contemporary literature. Recent findings: Penile cancer is a rare and aggressive neoplasm that accounts for less than 1% of male malignancies in the United States. Geographical disparities in incidence of disease are evident with high rates concentrated in the developing world (2.8–6.8 per 100 000) where neonatal circumcision is low and socioeconomic conditions predispose patients to multiple risk factors. Western countries have a significantly lower incidence and can be as low as 0.3 per 100 000. Many risk factors have been identified including lack of circumcision, phimosis, balanitis, obesity, lichen sclerosus, smoking, and psoralen UV-A phototherapy. In addition, human papilloma virus (HPV) has been linked to nearly 40% of cases and molecular mediators continue to be investigated. Summary: Although Penile cancer can be a debilitating disease, several of the known risk factors are modifiable. Public health campaigns aimed to increase awareness, promote better hygiene, and deploy HPV vaccines have had varied success at decreasing disease burden. Focus should be placed on implementing such interventions in developing countries and at-risk populations.